Analyzing Mathematical Problem Solving and Critical Thinking Abilities Through Problem Based Learning at Junior High School Students - Hayati, Nina; Mulyono, Mulyono; Surya, Edy; Lumbantobing, Happy (UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study was to determine the ability to solve problems and think critically through problem-based learning. The problem-based learning framework supports talent abilities by shaping students' thinking. This study involved students of class VIII-A SMP PGRI 4 Medan. The research approach used descriptive qualitative. SMP PGRI 4 Medan became the locus of the 2024/2025 research. This study used interviews and assessments of problem solving and critical thinking. The results showed that students' mathematical problem solving abilities averaged 65, which was moderate. Students' critical thinking averaged 66.9, which was moderate. The difficulties faced by students by comparing the results of the interview can be seen that students have difficulties in the four indicators of problem solving and critical thinking abilities. Where students ignore or do not recheck or draw conclusions and only concentrate on the solution procedure. This study shows that students have moderate problem solving and critical thinking skills when dealing with a system of linear equations of two variables.